2014
DOI: 10.1044/1092-4388(2013/13-0015
|View full text |Cite
|
Sign up to set email alerts
|

Vocal Function and Upper Airway Thermoregulation in Five Different Environmental Conditions

Abstract: Purpose Phonation threshold pressure and perceived phonatory effort were hypothesized to increase and upper airway temperature decrease following exposure to cold and/or dry air. Greater changes were expected with mouth versus nose breathing. Method Using a within-participant repeated measures design, 15 consented participants (7 men, 8 women) completed 20-minute duration trials to allow for adequate thermal equilibration for both nose and mouth breathing in five different environments: three temperatures (°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 53 publications
(89 reference statements)
0
5
0
1
Order By: Relevance
“…It has been suggested that environmental temperature may influence vocal function. 11 Twenty minutes of mouth breathing in hot, dry air does not increase PTP in vocally healthy participants. However, the effect of temperature on PTP during longer durations of mouth breathing has yet to be investigated and should be considered in the future.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It has been suggested that environmental temperature may influence vocal function. 11 Twenty minutes of mouth breathing in hot, dry air does not increase PTP in vocally healthy participants. However, the effect of temperature on PTP during longer durations of mouth breathing has yet to be investigated and should be considered in the future.…”
Section: Discussionmentioning
confidence: 94%
“…1 However, adverse voice changes following 15–20 minutes of mouth breathing in low humidity have not been observed consistently. 11,12 Individuals may regularly spend longer periods of time breathing in dry environments. 6 It is possible that more consistent voice changes will be observed following longer challenge durations.…”
mentioning
confidence: 99%
“…A su vez, la relevancia de estos resultados complementa la terapéutica del paciente con odinofonía. Gracias a esto, en algunos casos, se puede buscar el incremento en la ingesta de agua para mantener la temperatura del tracto vocal durante la fonación (Sandage, Connor, & Pascoe, 2014) o, en otros, se pueden especificar el abordaje manual para mantener al nervio laríngeo superior con el menor grado de compresión posible (Mathieson et al, 2009). La intensidad del dolor expresada por las participantes es en promedio, moderado (5 a 6).…”
Section: Discussionunclassified
“…The relation between environmental temperature and voice use intensity is still unclear. Nevertheless, previous studies on the influence of temperature in voice production have highlighted the association between temperature, and muscle function and laryngeal viscosity (27,28). Since regulation of vocal intensity is partly controlled by the tension of the vocal folds, it seems likely that a higher temperature reduces muscle tension of vocal folds and, thereby, increases the airflow during phonation and therefore the vocal intensity.…”
Section: Discussionmentioning
confidence: 99%